Perancangan Dan Simulasi Jaringan Virtual Wide Area Network Untuk Private Server Dengan Packet Tracer 6.01 - Putradianto, Adipta, Dr. Ir. Bana Handaga, M.T (2015)
Development of technology in the world always rapidly, directly proportional to the digital data storage needs, because currently more advanced technology of the data in the greater usage. Currently, many individuals or companies entrust their privacy data to online storage. However, there are also cases of online data theft from hackers who are not responsible also the occurrence of network disorder resulting in disruption of data distribution. For the example of the problem is the design of network in hospital, network design means that once had documentation of the network to which it important role in the development or maintenance. All simulated by a tracer packet include the connections between devices, web services, file services, and mail service. In the simulation connection can be simulated well how it work and a firewall that can filter network. Also manage the bandwidth required in router. That's all in the software packet tracer.